Innovation in family businesses: Exploring the influence of entrepreneurial orientation and absorptive capacity on innovative capacity - Felipe Hernández-Perlines; Alicia Blanco-González; Giorgia Miotto (Journal of Innovation & Knowledge (JIK), 2024)
Firms' innovation positively affects their competitiveness and thus their financial performance. To bridge the research gap in the theoretical framework of dynamic capabilities and respond to the call for papers to explore new ways of analyzing innovation in family businesses, this study investigates how entrepreneurial orientation and absorptive capacity influence innovative capacity in family firms. Data from 156 family firms are analyzed using the theoretical framework of dynamic capabilities and structural equation modeling. The results reveal that both entrepreneurial orientation and absorptive capacity influence innovative capacity and that this influence is greater when both capabilities act together than when they act individually. This study confirms that entrepreneurial orientation and absorptive capacity are antecedents of innovative capacity. Moreover, entrepreneurial orientation has a greater influence on innovative capacity than absorptive capacity does.
Keywords: M10; L21; O52; 650; Entrepreneurial orientation; Absorptive capacity; Innovative capacity; Family business; Dynamic capabilities